Adult’s veracity judgments of Black and White children’s statements: the role of perceiver and target race and prejudice-related concerns - Zanette, Sarah; Hagi Hussein, Siham; Malloy, Lindsay C. (Frontiers in Psychology, 2023)
Introduction: Seldom has work investigated systematic biases in adults' truth and lie judgments of children's reports. Research demonstrates that adults tend to exhibit a bias towards believing a child is telling the truth, but it is unknown whether this truth bias applies equally to all children. Given the pervasiveness of racial prejudice and anti-Black racism in the United States, the current study examined whether adults are more or less likely to believe a child is telling the truth based on the race of the child (Black or White), the race of the adult perceiver (Black or White), and the perceiver's concerns regarding appearing non-prejudiced. Methods: Using an online data-collection platform, 593 Black and White American adults reviewed fictitious vignettes of a child denying having committed a misbehavior at school (e.g., damaging a laptop). The race and gender of the child in the vignette were manipulated using an AI-generated photo of either a Black child or White child. After reading each story, participants provided a categorical veracity judgement by indicating whether they believed the child in the story was lying (and therefore committed the misdeed) or telling the truth (and was innocent), as well as rated how honest or deceptive the child was being on a continuous scale. Participants also completed questionnaires assessing their internal (personal) and external (normative) motivations to respond in non-prejudiced ways. Results and Discussion: Results indicated that systematic racial biases occur in adults' veracity judgments of children's statements. Both Black and White participants exhibited a truth bias in their veracity judgements of Black children, but they showed no such bias when evaluating the deceptiveness of White children. Consistent with the prejudice-related concerns hypothesis, the observed truth bias towards Black children was moderated by individual differences in participants' desire to respond without prejudice and whether those motivations stem from external or internal sources. The current findings present novel evidence regarding racial bias and prejudice-related concerns as potential barriers to making veracity judgements of children's statements and, ultimately, successful lie detection.